PENGARUH FAKTOR SOSIAL BUDAYA TERHADAP PRODUK PEMIKIRAN HUKUM ISLAM - Saidah, Saidah (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2016)
This paper discusses the influence of social cultural factors of some products of Islamic law in Indonesia by analyzing ideas of the scholars in the form of fiqh, fatwa, the judge's decision and laws in force in some Muslim countries. It is concluded that in the history of Islamic law, social and cultural factors have an important influence in coloring products of Islamic legal thought.